2012
DOI: 10.1007/s10753-012-9507-9
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Magnolol on Lipopolysaccharide-Induced Acute Lung Injury in Mice

Abstract: Magnolol, a tradition Chinese herb, displays an array of activities including antifungal, antibacterial, and antioxidant effects. To investigate the protective effect of magnolol on lipopolysaccharide (LPS)-induced acute lung injury (ALI) in mice. ALI was induced in mice by intratracheal instillation of LPS (1 mg/kg). The mice received intratracheal instillation of magnolol (5 μg/kg) 30 min before LPS administration. Pulmonary histological changes were evaluated by hematoxylin-eosin stain and lung wet/dry weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Moreover, inhibiting inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) expression, and NF-κB activation have been proposed to be associated with the protective effects of magnolol on LPS-induced acute lung injury and sepsis [16][17][18]. Our recent work has confirmed that magnolol is capable of preventing the alveolar bone resorption and oral tissue inflammation in an animal model of periodontitis [19].…”
Section: Introductionsupporting
confidence: 57%
“…Moreover, inhibiting inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) expression, and NF-κB activation have been proposed to be associated with the protective effects of magnolol on LPS-induced acute lung injury and sepsis [16][17][18]. Our recent work has confirmed that magnolol is capable of preventing the alveolar bone resorption and oral tissue inflammation in an animal model of periodontitis [19].…”
Section: Introductionsupporting
confidence: 57%
“… Compounds Structure In vitro/in vivo Model (effective dose) Cells (effective concentration) Related pharmacological indicators Related molecular mechanisms Refs. Honokiol 91 CLP/LPS (5 mg/kg) HPMECs (5 μM) MPO↓ TNF-α↓ IL-6↓ MDA↓ iNOS↓ ICAM-1↓ NO↓ HMGB1↓ Activation of Sirt3/AMPK signaling axis [ [283] , [284] , [285] ] Paeonol 92 LPS (0.146 mg/kg) MPO↓ TNF-α↓ IL-1β↓ IL-6↓ HMGB1↓ Inhibition of HMGB1 and TLR4/MyD88/NF-κB signaling pathway [ 286 , 287 ] Magnolol 93 LPS (10 mg/kg) MPO↓ TNF-α↓ IL-1β↓ IL-6↓ COX-2↓ iNOS↓ Activation of PPAR-γ Inhibition of TLR4 mediated NF-kB signaling pathway [ [288] , [289] , [290] , [291] ] Curcumin 94 Bleomycin/LPS/CLP/Lethal gramnegative (150 mg/kg) TNF-α↓ IL-1β↓ IL-6↓ TGF-β↓ HMGB1↓ IL-17A↓ IL-10↑ Inhibition of IL-17A mediated p53-fibrinolytic system, PPARγ/HO1 regulated-HMGB1/RAGE, MAPK signaling pathway, TGF-β1/SMAD3 signaling pathway and NF-κB pathways [ [292] , [293] , [294] , [295] , [296] , [297] , [298] ] Zingerone 95 LPS (20 mg/kg) RAW 264.7 (12.5 μg/mL) MPO↓ TNF-α↓ IL-1β↓ IL-6↓ Inhibition of NF-κB and MAPK signaling pathways [ 299 ] Octyl gallate 96 ...…”
Section: Mechanisms Involved In Ali/ardsmentioning
confidence: 99%
“…et Wils. Due to anti-inflammatory activity, magnolol markedly attenuated the histological alterations, reduced inflammatory cell infiltration, decreased lung edema as well as down-regulated pro-inflammatory mediator expression (TNF-α, IL-1β, IL-6, iNOS and COX-2), which were induced by blocking TLR4-mediated NF-κB signaling pathways and activating PPARγ [ [288] , [289] , [290] , [291] ].…”
Section: Natural Compounds That Exert Anti-ali Effectsmentioning
confidence: 99%
“…Magnolol (5,5′-di-2-propen-1-yl-2,2′-Bichavicol) is a lignan exacted from the bark of Magnolia officinalis , the compounds of which demonstrating anti-cancer, anti-stress, anti-anxiety, anti-depressant, anti-oxidant and anti-inflammatory effects [ 8 ]. The anti-inflammatory effect of magnolol has been reported in the animal models of ischemic stroke [ 9 ], oxygen-induced retinopathy [ 10 ], acute lung injury [ 11 , 12 ], mastitis [ 13 ], and arthritis [ 14 ]. In RAW264.7 cells, magnolol can inhibit lipopolysaccharide (LPS)-induced NF-κB activation, IKBα degradation and pro-inflammatory cytokines production [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%